Vesicular stomatitis virus mutants resistant to defective-interfering particles accumulate stable 5'-terminal and fewer 3'-terminal mutations in a stepwise manner. - O'Hara, P J (1984)
We have studied the evolution of sequences which include the RNA polymerase binding sites at the 5' and 3' termini of vesicular stomatitis virus mutants (Sdi-) resistant to defective-interfering particles. We observed a striking stepwise accumulation of stable base substitutions within the area of replication initiation at the 5'-terminal 54 nucleotides of Sdi- mutants isolated at intervals from persistent infections and undiluted lytic passage series. Fewer mutations accumulated in the region of transcription initiation at the 3' end and in those portions of the N and L protein coding cistrons examined. The termini changes are not strictly required to obtain the Sdi- phenotype. However, it is possible that they represent stepwise compensatory changes to accommodate Sdi- mutations affecting viral replication or encapsidation gene products or both. These results have important implications for RNA virus genome evolution.